2017
DOI: 10.1186/s12889-017-4584-1
|View full text |Cite|
|
Sign up to set email alerts
|

Implementation-effectiveness trial of an ecological intervention for physical activity in ethnically diverse low income senior centers

Abstract: BackgroundAs the US population ages, there is an increasing need for evidence based, peer-led physical activity programs, particularly in ethnically diverse, low income senior centers where access is limited.Methods/designThe Peer Empowerment Program 4 Physical Activity’ (PEP4PA) is a hybrid Type II implementation-effectiveness trial that is a peer-led physical activity (PA) intervention based on the ecological model of behavior change. The initial phase is a cluster randomized control trial randomized to eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Studies show that older adults are able to operate tablets better than personal computers [20,21] or smartphones owing to their large touchscreen [22]. It is not surprising that recent health interventions for older adults choose tablets as the primary mode of delivery [23-27].…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that older adults are able to operate tablets better than personal computers [20,21] or smartphones owing to their large touchscreen [22]. It is not surprising that recent health interventions for older adults choose tablets as the primary mode of delivery [23-27].…”
Section: Introductionmentioning
confidence: 99%
“…Systematic reviews from intervention studies based on the SEM have revealed the effectiveness of such interventions, indicating that not only PA level was increased, but sedentary time was reduced ( 25 , 26 ). It is noteworthy that many current studies have condensed the SEM into three levels: individual, interpersonal, and community levels ( 27 , 28 ). Our detailed interventions based on the three levels (individual, interpersonal, and community levels) are as follows ( Figure 1 ):…”
Section: Methodsmentioning
confidence: 99%
“…Participants presented selected projects to transportation engineers, submitted online requests through a municipal website, and/or called elected officials. The curriculum for the physical activity condition used an adapted evidence-based program for older adults [ 22 ] and included group exercise plus behavior change strategies, such as goal setting, social support, and positive thinking for increasing physical activity. The 8-week intervention concluded in November 2016.…”
Section: Methodsmentioning
confidence: 99%